Chronic vagus nerve stimulation in Crohn's disease: a 6‐month follow‐up pilot study. Issue 6 (27th February 2016) - Bonaz, B.; Sinniger, V.; Hoffmann, D.; Clarençon, D.; Mathieu, N.; Dantzer, C.; Vercueil, L.; Picq, C.; Trocmé, C.; Faure, P.; Cracowski, J‐L.; Pellissier, S.
Abstract: The vagus nerve (VN) is a link between the brain and the gut. The VN is a mixed nerve with anti‐inflammatory properties through the activation of the hypothalamic–pituitary–adrenal axis by its afferents and by activating the cholinergic anti‐inflammatory pathway through its efferents. We have previously shown that VN stimulation (VNS) improves colitis in rats and that the vagal tone is blunted in Crohn's disease (CD) patients. We thus performed a pilot study of chronic VNS in patients with active CD. Seven patients under VNS were followed up for 6 months with a primary endpoint to induce clinical remission and a secondary endpoint to induce biological (CRP and/or fecal calprotectin) and endoscopic remission and to restore vagal tone (heart rate variability). Vagus nerve stimulation was feasible and well‐tolerated in all patients. Among the seven patients, two were removed from the study at 3 months for clinical worsening and five evolved toward clinical, biological, and endoscopic remission with a restored vagal tone. These results provide the first evidence that VNS is feasible and appears as an effective tool in the treatment of active CD. Abstract : Vagus nerve stimulation is feasible and appears as an interesting tool in the treatment of active Crohn's disease (CD) but further investigation in a larger longitudinal cohort of CD patients is warranted. Our aim was to perform a pilot study of chronic vagus nerve stimulation (VNS) in patients with active CD. Seven patients under VNS were followed up for 6 months with a primary endpoint to induce clinical, biological, and endoscopic remission and to restore vagal tone. Vagus nerve stimulation was well‐tolerated in all patients. Five patients evolved toward clinical, biological, and endoscopic remission with a restored vagal tone.